Newly synthesized piperazine derivatives as tyrosinase inhibitors: in vitro and in silico studies - ERDEM, SAFİYE (My University, 2022)
In this study, a series of new organic compounds with piperazine as a fundamental skeleton was synthesized and evaluated for their tyrosinase inhibitory potentials by in vitro and in silico studies. The in vitro studies have shown that compounds 10a and 10b bearing 1,2,4, triazole nucleus could be considered potent tyrosinase inhibitors with IC50 values of 31.2 +/- 0.7 and 30.7 +/- 0.2 mu M, respectively. 10b (K-i = 9.54 mu M, mixed type inhibition) with the lowest IC50 value among derivatives was selected to determine kinetic constants and inhibition types. Furthermore, molecular docking analysis was performed for all compounds and it was observed that 4b, 5a, 4c, and 10b showed promising inhibitory effect on tyrosinase activity. Based on docking results, ADME predictions and in vitro studies, 10b might be considered suitable oral drug candidates for further studies.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Chemistry (miscellaneous); General Chemistry; Physical Sciences; Tyrosinase inhibitor; Piperazine; Triazole; Molecular docking; DIPHENOLASE ACTIVITIES; BIOLOGICAL EVALUATION; DENSITY FUNCTIONALS; MOLECULAR DOCKING; MONOPHENOLASE; KINETICS; DESIGN; SERIES; AGENTS